Inocybe hopeae sp. nov. and first record of Pseudosperma keralense (Inocybaceae) from Thailand - Raghoonundon, Bhavesh; Vadthanarat, Santhiti; Hu, Yuwei; Raspé, Olivier (European Journal of Taxonomy, 2023)
Based on genetic studies, supported further by morphological and ecological differences, we present a taxonomic novelty (Inocybe hopeae Raghoonundon & Raspé sp. nov.) and a new geographical record (Pseudosperma keralense) from forests of Northern Thailand. Inocybe hopeae is characterized by medium-sized basidiomes, brownish orange to brown pileus that is darker towards the margin, off-white to pale brown context, light brown to dark brown stipe with off-white basal mycelium and pale brown to grayish brown lamellae. A three-gene phylogeny (LSU, tef1, rpb2) coupled with macroscopic / microscopic descriptions and illustrations are provided confirming the species’ positions in their respective generic clades. Inocybe hopeae was sister to I. thailandica with strong support (BS = 100%, PP = 1.0). Our Thai collections of OR1629 had similar morphological characters and 100% identical sequences with the holotype of Pseudosperma keralense from India.